The impact of off-balance sheet items on banks’ total factor productivity: empirical evidence from the Chinese banking sector - Sufian, Fadzlan (Inderscience Publishers, 2009)
By employing the Malmquist Productivity Index (MPI) method, this paper attempts to examine the impact of Off-Balance Sheet (OBS) items on Chinese banks’ total factor productivity. The results suggest that state-owned, joint stock and city commercial banks have exhibited lower Total Factor Productivity Change (TFPCH) levels with the inclusion of off-balance sheet items. We find that state-owned and city commercial banks have exhibited lower TFPCH due to Technological Change (TECHCH), while joint stock commercial banks have exhibited lower TFPCH due to Technical Efficiency Change (EFFCH). The empirical findings suggest that the inclusion of off-balance sheet items has resulted in higher EFFCH levels for both state owned and city commercial banks due to higher Scale Efficiency Change (SECH), while joint stock commercial banks have exhibited lower EFFCH due to Pure Technical Efficiency Change (PEFFCH).